Effect of ion supplementation of a commercial soft drink on tooth enamel erosion - Magalhaes, A. C. [UNESP]; Moraes, S. M.; Rios, D.; Buzalaf, M. A. R. (Taylor & Francis Ltd, 2009)
Acidic soft drinks are potentially erosive for dental hard tissues. This in vitro study evaluated the effect of calcium, fluoride, iron and phosphate, supplemented alone or in combination to a commercial citric acid-based carbonated beverage on dental erosion. Ninety enamel samples (4 x 4 x 3 mm) were randomly allocated to nine groups (n = 10): G1 - pure beverage (control); G2 - with 1 mM Ca; G3 - with 0.047 mM F; G4 - with 1 mM Fe; G5 - with 1 mM P; G6 - with 1 mM Ca and 0.047 mM F; G7 - with 1 mM Ca and 1 mM P; G8 - with 1 mM Fe and 0.047 mM F; and G9 - with 1 mM Ca, 1 mM P, 0.047 mM F and 1.0 mM Fe. The samples were subjected to six pH cycles over a 24-h period. In each cycle, the samples were immersed in pure or modified beverage (1 min) and in artificial saliva (59 min). During the remaining period (18 h), the samples were maintained in artificial saliva. Enamel loss was assessed by profilometry (mm). Data were tested using ANOVA and Tukey's tests (p < 0.05). Highest enamel losses were observed in the control group (G1) and in the groups containing Fe (G4 and G8). The groups containing Ca (G2 and G6) showed significantly less wear compared to control. In conclusion, the modification of an erosive soft drink with low concentrations of Ca with or without F may reduced its erosive potential.
Keywords: calcium; dental erosion; enamel; fluoride; iron; phosphate